Critical Discourse Analysis on a Text “Friday Prayer at Home for Most but Some Risk Infection at Mosques” by the Al Jazeera English - Erlan Aditya Ardiansyah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2020)
This study aimed to investigate a discourse conveyed in an article entitled “Friday Prayer at Home for Most but Some Risk Infection at Mosques” by a news agency namely Al Jazeera English (AJE) relating to prohibition of the Friday Prayer in many countries and power presented by the certain countries due to prevent Covid-19. This study applied a descriptive-qualitative method. This study used Fairclough (1995; 2004) three-dimensional critical discourse analysis (CDA). The results were observed through micro-, meso-, and macro-levels of analyses. Data analysis performed by using the microlevel of analysis showed that the text contains active transitive structure to demonstrate subjects of the sentences. The study found that there are words which mostly appear in the text such as Muslim and prayers. In the mesolevel of analysis, intertextual analysis describes that there are assumption in the text. The data also depict that people showed disobedience to the governmental regulation and the worshippers still practiced prayers at home which caused irony in the discourse. The macrolevel of analysis illustrates the text published by the AJE generally converse updated issues because people recognize the news agency with a good reputation. The study concluded that the text mainly discussed the prohibition of communal prayers by many countries which is originated from other related texts. Keywords: Critical discourse analysis, covid-19, Muslim prayers, power